PERANSERTA : ADMINISTRASI KEUANGAN SEDERHANA BAGI UMKM DAERAH KAMPUNG TIMUR KELURAHAN GUNUNG SAMARINDA BALIKPAPAN - Anam, Hairul (Jurnal Abdi Masyarakat Ilmu Ekonomi (JAMIE), 2025)
Known as Kampung Timur, it is located in Gunung Samarinda Village, North Balikpapan Sub-district. The location of Kampung Timur is very strategic, meeting the direction of Muara Rapak Village on Soekarno Hatta Road with the Wika Housing Complex, and the Public Vehicle Terminal and Grand City Sinar Mas Balikpapan. This area is very rapidly growing, especially the world of Micro Small and Medium Enterprises where along the road can be seen and can be enjoyed various culinary and micro small and medium business stalls. Micro Small Medium Entrepreneurs thrive in the eastern village location, and for that innovation and creativity are needed in the future so that it can be an alternative profitable choice, In line with the development of the city and the business it is necessary to support simple financial administration patterns for Micro Small Medium Enterprises to be able to exist more in the future in the digitalization era.